2014
DOI: 10.1080/10911359.2013.873755
|View full text |Cite
|
Sign up to set email alerts
|

Family Resilience Predicts Socioeconomic Mobility of HUD Participants

Abstract: Changing economic times and government policies are reshaping the way the U.S. Department of Housing and Urban Development (HUD) provides services nationwide; there is both a growing demand for housing and a desire to help families become self-sufficient. In this study, the authors examined factors that contribute to increased socioeconomic mobility through the lens of family resilience. Analyzing cross-sectional data from 411 families in the San Bernardino County HUD District using discriminant function analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…In this review, 15 assessments were identified as having frequent use in the literature, yet not one of these assessments contained both a robust (comprehensive) analysis of resilience while also being psychometrically strong, leading to the conclusion that currently there is no gold standard for assessing resilience at multiple levels. Additionally as noted by previous researchers, to cover all of the concepts in Table 1 a researcher would have to employ upwards of 27 different assessments (McCubbin, Thompson, & McCubbin, 1996;Stiel, Estrella, Wang, & Distelberg, 2014). Currently no known study has included all of the concepts in Table 1 in one evaluation.…”
Section: Creating a Useful And Practical Measurementmentioning
confidence: 97%
See 1 more Smart Citation
“…In this review, 15 assessments were identified as having frequent use in the literature, yet not one of these assessments contained both a robust (comprehensive) analysis of resilience while also being psychometrically strong, leading to the conclusion that currently there is no gold standard for assessing resilience at multiple levels. Additionally as noted by previous researchers, to cover all of the concepts in Table 1 a researcher would have to employ upwards of 27 different assessments (McCubbin, Thompson, & McCubbin, 1996;Stiel, Estrella, Wang, & Distelberg, 2014). Currently no known study has included all of the concepts in Table 1 in one evaluation.…”
Section: Creating a Useful And Practical Measurementmentioning
confidence: 97%
“…We tested the IFCR's predictive validity by measuring the IFCR's ability to discriminate within the sample those that were employed full time, those that were not employed, and those that were engaged in activities that were likely to lead to full-time employment. In a previous study (Stiel et al, 2014) the authors provided a protocol for how to construct an objective variable that would parallel the common Moving to Work housing program policies for measuring a family's current employment status. More specifically families are categorizes as compliant, contingent, and IFCR noncompliant with the Moving to Work policies to maintain full-time employment.…”
Section: Measures Used For Validity Estimatesmentioning
confidence: 99%
“…Strengthening family resilience processes through interventions have been shown to encourage transformation and growth (Acuña & Kataoba, 2017;Stiel et al, 2014;Vermeulen & Greeff, 2015). Multiple positive outcomes have been reported because of family-based research and interventions.…”
Section: Background and Rationalementioning
confidence: 99%
“…Interestingly, some studies have found that there is also more to the success of a well‐rounded family system than the mere addition of resources. Stiel, Estrella, Wang, and Distelberg's () study found intangible resources such as adequate social support was an essential component of the success of resource‐focused programs. The study evaluated 411 families who were enrolled within a resource‐focused Family Self‐Sufficiency Programme in California.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation